Lipase‐catalyzed interesterification reactions for human milk fat substitutes production: A review. Issue 3 (13th February 2013) - Soumanou, Mohamed M.; Pérignon, Marlène; Villeneuve, Pierre
Abstract The synthesis of human milk fat substitutes (HMFS) which show a high degree of similarity to human milk fat (HFM) is of great interest to ensure a supply in infant nutrition with a triacylglyceride composition as close as possible to mothers milk. Biocatalyzed modifications of natural oils using microbial or plant‐derived enzymes enable the production of high‐value HMFS. Due to the mild reaction conditions and the exceptionally high sn‐1, 3‐regioselectivity of these enzymes, they are preferred over chemical catalysis in the development of these lipids with desired nutritional and functional properties. In this article, research spanning over 20 years of lipase‐catalysis for the production HMFS is reviewed. Specific attention is paid to the evaluation of the regiospecificity of the biocatalysts, choice of natural oils and acyl donors, production processes, purification of the HMFS, and analytical procedures for their characterization.